Fostering Critical Thinking in Early Childhood: Teacher Scaffolding Strategies for Children Aged 5–6 - Annisa Tri Ananda Dewi; Naura Nadhifah; Prafitriyani Putri; Zayyidatur Rohmah; Aqna Rahma Atika (Early Childhood Development Gazette, 2026)
Critical thinking is an essential skill that needs to be developed from an early age to support children’s cognitive development and problem-solving abilities. This study aims to explore teacher scaffolding strategies in fostering critical thinking among children aged 5–6 years in early childhood education settings. The research employed a qualitative approach using a case study design. Data were collected through classroom observations, teacher interviews, and documentation of learning activities. The data were analyzed using an interactive analysis model consisting of data condensation, data display, and conclusion drawing and verification. The findings reveal that teachers apply several scaffolding strategies to stimulate children’s critical thinking, including questioning techniques, guided interaction, modeling, and gradual assistance. These strategies encourage children to express ideas, analyze situations, and develop simple problem-solving abilities during learning activities. The study implies that effective scaffolding practices can create interactive learning environments that support children’s cognitive engagement and critical thinking development. Therefore, integrating scaffolding strategies into daily teaching practices is important for promoting meaningful learning experiences and supporting early childhood cognitive development.